Analysis of the Mechanism of Determining Selling and Service Prices in the Islamic Economic Perspective - Siti Muslihatun (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2020)
The purpose of this study was to find out how the mechanism for determining the selling price and services on Photocopying and Printing Ammey Kel. Dermayu Kab. During Prov. Bengkulu and to find out how the Islamic economic review of the mechanism for determining the selling price and services on the Ammey Photocopy and Printing. To reveal these problems in depth and comprehensively, the authors use qualitative methods to collect the necessary information during the research period. The data collection of this research was carried out by conducting observations or observations and interviews, with the object of research in Photocopying and Printing Ammey. Based on the results of research and analysis on the mechanism for determining selling prices and services in Ammey Photocopying and Printing, it can be concluded that the mechanism for determining price rounding is unclear in Photocopying but Ammey Printing uses fairness-based pricing, pricing in Ammey Photocopy and Printing is in accordance with the principle Islamic economics because the price set does not oppress buyers, namely Photocopying and Printing Ammey takes advantage at a reasonable level. Photocopying and Printing Ammey does not take advantage of the rounding off of the price, but the remainder of the rounding proceeds will be collected and transferred to social funds and to mosque charity boxes.